2006
DOI: 10.1103/physrevd.74.053011
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Randall-Sundrum geometric origin of flavor with lepton flavor violation

Abstract: The "anarchic" Randall-Sundrum model of flavor is a low energy solution to both the electroweak hierarchy and flavor problems. Such models have a warped, compact extra dimension with the standard model fermions and gauge bosons living in the bulk, and the Higgs living on or near the TeV brane. In this paper we consider bounds on these models set by lepton flavor violation constraints. We find that loop-induced decays of the form l → l ′ γ are ultraviolet sensitive and uncalculable when the Higgs field is local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
588
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(612 citation statements)
references
References 38 publications
23
588
1
Order By: Relevance
“…This is expected since the 5D theory is non-renormalizable with negative mass dimension operators. For instance, when the Higgs is localized on the IR brane, the above one-loop is divergent, and a counter-term in the form of a higher dimensional IR operator is included [3,15,16]. We can derive a bound on the corresponding cutoff of the theory required to satisfy the constraints from b → sγ and / K (similarly to the µ → eγ case [16]).…”
Section: The Case Of An Ir-brane Higgs With Uv Sensitive Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected since the 5D theory is non-renormalizable with negative mass dimension operators. For instance, when the Higgs is localized on the IR brane, the above one-loop is divergent, and a counter-term in the form of a higher dimensional IR operator is included [3,15,16]. We can derive a bound on the corresponding cutoff of the theory required to satisfy the constraints from b → sγ and / K (similarly to the µ → eγ case [16]).…”
Section: The Case Of An Ir-brane Higgs With Uv Sensitive Operatorsmentioning
confidence: 99%
“…where i, j are flavour indices and m, n are the KK levels of the fermions in the loop, and we only consider the first KK state, since at one-loop the above contribution is finite (or at most log-divergent) [3,15,16]. Following the analysis in [9] (allowing 20% departure from the SM value of B(B → X s γ)) and using the values of the quark Yukawa couplings at 5 TeV [14], we obtain for β = 1 by requiring…”
Section: Rs Contributions To K and B → Sγmentioning
confidence: 99%
“…While most of the flavor literature in WED has been devoted to the quark sector, the lepton sector has also been extensively explored [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]32]. In fact the lepton sector is qualitatively different from the quark sector as the charged lepton spectrum is hierarchical while the neutrino spectrum and PMNS mixing angles are mostly anarchical [33].…”
Section: Jhep02(2013)079mentioning
confidence: 99%
“…Generically there are two types of LFV sources: tree-level LFV via the exchange of heavy neutral particles (like Z') or off-diagonal Z couplings, or loop induced rare decays via charged current interactions. Tree-level LFV operators have been considered in [11], and it was found that the lepton flavor scale is at least 5 TeV, and larger for smaller brane Yukawa couplings. We will first show here that the structure of the A 4 symmetry used here is such that all tree-level sources of lepton flavor violation are absent in this theory.…”
Section: Numerical Scans and Electroweak Precision Boundsmentioning
confidence: 99%
“…While these flavor violations are suppressed by the so-called RS-GIM mechanism [6,8], the KK mass scale still has to be as large as 20 TeV in order to safely suppress FCNC's in the quark sector [9]. In the lepton sector the anarchic approach [10] imposes a bound of order 10 TeV on the KK mass scale [11]. These bounds imply that the theory is out of reach for the LHC and unlikely to be useful for solving the (little) hierarchy problem.…”
Section: Introductionmentioning
confidence: 99%